Evolving impacts of the COVID-19 pandemic on micro, small, and medium-sized enterprises in Asia - Takiko Igarashi; Asami Takeda; Hoa Thi Truong; Tetsushi Sonobe (Asian Development Bank Institute (ADBI), 2021)
Since the first quarter of 2020, micro, small, and medium-sized enterprises (MSMEs) in developing countries have faced significant hardship due to the economic shocks related to the COVID-19 pandemic. Questions arise, however, regarding the extent to which MSMEs' hardship has varied between sectors and between countries over time, whether it is gender neutral, whether the digitalization of MSMEs could alleviate it, and whether government support has reached MSMEs. This paper aimed to answer these questions using new survey data from eight developing Asian countries around the middle and toward the end of 2020. We found a wide variation in the severity of and responses to the pandemic impacts on MSMEs between sectors and between countries. Turning to common trends, our significant findings were as follows. First, MSMEs' sales and non-permanent employment tended to recover toward late 2020. Second, despite the general trend, the pandemic shocks concentrated on hard-hit industries, such as food processing, textiles, tourism, food and drink services, and education, which even deteriorated in the second half of 2020. Third, women-led enterprises remained vulnerable, exhibiting bleak prospects for sales or more job cuts than men-led but otherwise similar enterprises. Fourth, the digitalization intensity had a nonlinear relationship with MSMEs' sales and employment, suggesting that online sales beyond a certain threshold, around 40% of the total sales, could generate more revenues and jobs for MSMEs. Last, the number of MSMEs receiving support from their governments increased in the second half of 2020. Still, such support did not effectively reach the most affected or vulnerable MSMEs.
Keywords: D22; J63; L25; O53; 330; COVID-19; micro; small; and medium-sized enterprises (MSMEs); layoffs; cash shortage; digitalization